LIDAR POINT CLOUD COMPRESSION - HAYES, JOHN (2011)
Using LIDAR technology, terabytes of data are generated which form massive point clouds. Such rich data is a blessing for signal processing and analysis but also is a blight, making computation, transmission, and storage prohibitive. The disclosed subject matter includes a technique to convert a point cloud into a form that is susceptible to wavelet transformation permitting compression that is nearly lossless.